UJI COBA EVALUASI KINERJA GURU - GURU DI SDN X MENGGUNAKAN RANGKING METHOD - Muhammad Rizki Priantono; Tomi Irawan; Syamsul Hidayat (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Theoretically, the results of this research discussion are expected to provide scientific contributions to the development of science, provide suggestions to schools and other parties in terms of better teacher performance. This study uses a ranking method. by using this method where teacher performance is ranked from the best to the worst. Data were obtained by conducting interviews and direct observations at the school. Data were obtained to analyze teacher performance in improving teacher performance so that teacher performance after this evaluation can be even better. The research subjects were 10 people at SDN X. Based on the data obtained, it can be concluded as follows: regarding absenteeism, teaching responsibility, teacher creativity in teaching, teaching quality and teacher discipline in coming to school. Thus, it is hoped that this evaluation will be able to change teacher performance to be better in the future.